TECHNIQUES FOR DESIGNING REGULATIONS AND LEGISLATION - Bambang Harianto; Inka Edriani; Sofian (Journal of International Islamic Law, Human Right and Public Policy, 2023)
Legislative regulations are written regulations formed by state institutions or authorized officials and are generally binding. In realizing national legal development policies, especially statutory regulations and realizing the orderly formation of statutory regulations by paying attention to general principles and the hierarchy of statutory regulations, Law Number 15 of 2019 concerning the formation of statutory regulations has been promulgated. However, looking at the aspect of the development of legislative regulations from year to year, it can be felt that there are weaknesses in the law and there are several other issues that are why the law is often subject to judicial review. To overcome this, it is necessary to evaluate the drafting of future legislation and the need to respond to various developments in state and government life as well as the dynamics occurring in society and so on.